Flood Impact Mitigation and Resilience Enhancement - Huang, Guangwei (IntechOpen, 2020)
The concept of resilience has been gaining momentum in various fields in recent years and has been used in various ways from a catch phrase to a cornerstone in theoretic development or practical operation. No matter how it is used, it does contribute one way or another to the refinement and application of the concept. This book focuses on the application of the resilience concept to flood disaster management. This book is a collection of research works conducted across the world and across sectors. Therefore, it is a good example of how different perspectives can catalyze our insight into complex flood-related issues. It can be considered valuable reading material for students, researchers, policymakers and practitioners, because it provides both the fundamentals and new development of resilience-based approaches and delivers a message that the goal of resilience-based flood management goes beyond disaster reduction.